bilateral fracture In the verses of the causal prohibition Functional vision (Journal of the College of Basic Education, 2022)
This paper deals with the phenomenon of exchanging roles between predications and complements in what I call the (causal prohibition) phrases.The analysis of the examples of (causal prohibition) in the Quran depends on the functional view, exemplified by one of the most popular personalities in functional grammar, i.e. Martinet.The paper consists of two sections, preceded by an introduction and followed by a conclusion. The first section is concerned with the theoretical data, whereas the second is concerned with the applications